Advancement in Shampoo (A Dermal Care Product): Preparation Methods, Patents and Commercial Utility - Deeksha; Malviya, Rishabha; K. Sharma, Pramod (Recent Patents on Inflammation & Allergy Drug Discovery, 2014)
Shampoo is a cleaning aid for hair and is the most evolving beauty products in the present scenario. Today’s shampoo products are of great importance as they provide cleaning of hair with the benefits of conditioning, smoothing and good health of hair i.e. dandruff, dirt, grease and lice free hair. Various types of shampoos depending upon function, nature of ingredient, and their special effects are elaborated in this study. Generally shampoos are evaluated in terms of physical appearance, detergency, surface tension, foam quality, pH, viscosity, and percent of solid content, flow property, dirt dispersion, cleaning action, stability and wetting time. The attention should be paid at its patent portion which attracts towards itself as it provides wide knowledge related to shampoo. This article reviews the various aspects of shampoo in terms of preparation methods, various patents and commercial value.
Keywords: dermal preparation